2016
DOI: 10.1007/s13402-016-0282-8
|View full text |Cite
|
Sign up to set email alerts
|

High glucose and insulin enhance uPA expression, ROS formation and invasiveness in breast cancer-derived cells

Abstract: From our data we conclude that hyperglycemia and hyperinsulinemia can promote breast cancer cell proliferation, migration and invasion. We found that these features were associated with increased expression of the mesenchymal markers vimentin and fibronectin, as well as increased uPA expression and activation through a mechanism mediated by ROS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 76 publications
1
44
0
Order By: Relevance
“…Diabetes itself might have a direct effect on breast cancer prognosis due to physiological effects of hyperglycemia, or hyperinsulinemia, which is a hallmark of insulin resistance commonly observed in patients with type 2 diabetes [28,29]. It has been shown that cancer-specific survival was decreased for women with abnormal glycemic status [25,27] and that fasting insulin levels are associated with worse outcome (distant recurrence and death), independent of Body Mass Index (BMI) [30].…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes itself might have a direct effect on breast cancer prognosis due to physiological effects of hyperglycemia, or hyperinsulinemia, which is a hallmark of insulin resistance commonly observed in patients with type 2 diabetes [28,29]. It has been shown that cancer-specific survival was decreased for women with abnormal glycemic status [25,27] and that fasting insulin levels are associated with worse outcome (distant recurrence and death), independent of Body Mass Index (BMI) [30].…”
Section: Introductionmentioning
confidence: 99%
“…PAI‐1 is expressed in mature TGCs in vivo (Teesalu, Blasi, & Talarico, ) and in vitro (Harvey et al, ). Increased levels of PAI‐1 expression have been associated with increased invasiveness of cancer cells (Flores‐López, Martinez‐Hernandez, Viedma‐Rodriguez, Diaz‐Flores, & Baiza‐Gutman, ; Kwaan, Mazar, & McMahon, ). According to our results, HG enhances the expression levels of PLAU, MMP‐9, and PAI‐1 in several cancer cell lines, and these proteins have been correlated with higher migratory and invasive ability (Flores‐López et al, ; Lin et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Increased levels of PAI‐1 expression have been associated with increased invasiveness of cancer cells (Flores‐López, Martinez‐Hernandez, Viedma‐Rodriguez, Diaz‐Flores, & Baiza‐Gutman, ; Kwaan, Mazar, & McMahon, ). According to our results, HG enhances the expression levels of PLAU, MMP‐9, and PAI‐1 in several cancer cell lines, and these proteins have been correlated with higher migratory and invasive ability (Flores‐López et al, ; Lin et al, ). Trophoblast and tumor cells have similar characteristics, including the increased expression of proteases that may play active roles in migration and invasion (Ferretti, Bruni, Dangles‐Marie, Pecking, & Bellet, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 Increased expression of ROS is found in most of cancers including the breast cancer cells. 24 While the increased expression of ROS is observed in cancer cells, recent studies show an interesting observation that the cancer stem cells have reduced expression of ROS. 25 With less ROS, cancer stem cells can evade the ROS mediated apoptosis, which makes them to survive better than cancer cells.…”
Section: Ros and Cancermentioning
confidence: 99%